Estoque de carbono em floresta tropical sazonalmente seca no nordeste do brasil: uma comparação entre dois usos do solo - Feitosa, Ramon Costa (2017)
The objective of this study was to evaluate the effect of land use and occupation and climatic seasonality on the forest structure, biomass and carbon stock of the arboreal shrub, necromass and soil. The work was developed at the Vale do Curu Experimental Farm (FEVC), domain property of the Federal University of Ceará (UFC), located in the municipality of Pentecoste, located in the Curu basin. The study was conducted in two fragments of tropical seasonally dry forests: Caatinga in Regeneration 32 years ago (CR) and Caatinga Sob Pastejo animal 32 years ago (CSP). The variables sampled were: number of shrub individuals, relative density, relative frequency, coverage value index, importance value index, Shannon index, Jaccard similarity, Jackknife richness estimator, arboreal shrub biomass, precipitation, necromass (K), root biomass and total organic carbon (TOC) of the soil in the layers 0-10 cm, 10-20 cm and 20-30 cm depth. The study was carried out between July/2014 and July/2016, a period divided into five collection seasons. The data were submitted to the analysis of non-parametric tests of Mann Whitney and Friedman (p ≤ 0,05). In the CR, 3,328 ind ha-1 were represented by 18 species and 10 families, which resulted in the carbon stock of 1.69 Mg ha-1 year-1. In the CSP, 2,821 ind ha-1 were subdivided into 12 species and 6 families, resulting in a carbon stock of 1.38 Mg ha-1 year-1. In addition to the differences caused by land use and occupation, rainfall stations determine the seasonality of the carbon stock, as seen in the period of low rainfall (July / March), the average annual increment is only 16% in relation to the rainy season (March /July). The carbon stock in necromass (dead trees and litter) was 4.36 Mg ha-1 in CR and 0.65 Mg ha-1 in CSP. In the two studied areas the necromass represented by the death of the trees represented 80% of the total carbon stored in this reservoir. Soil TOC and root biomass tend to reduce their quantity significantly with depth. Among the subterranean compartments studied, the TOC corresponded to 95% and 94% of the total stored in the soil in CR and CSP, respectively. This gave the TOC of the soil the title of the main underground carbon reservoir.